Design and optimization of spin micro-generator's rotating rack used in trajectory correction fuze under high-impact loadings. (July 2019) - Hui, Jianghai; Gao, Min; Li, Xinpeng
Buffer structure is a traditional measure to improve the ammunition's performance of withstanding impact loadings during launch process. On that basis, this paper proposes a parametric optimization for the gasket, which is served as buffer structure in spin microgenerator's rotating rack used in trajectory correction fuze to effectively reduce the stress of bearings used in the rack. It is a finite element dynamic simulation based on rack-projectile-barrel coupling to acquire variation of the bearings' stress. A rack-projectile-barrel coupling model is built and the simulation pre-process is described. At first, the parametric analysis for the gasket is conducted. The effect of the gasket's axial thickness and elastic modulus on the bearings' stress is studied, and the results show that singly changing one of the two gasket's parameters cannot effectively reduce the two-ball bearings' stress. Then, based on the two gasket's parameters, the design of experiment method is applied with 25 sample points established. A kind of approximation, response surface model is created and its fitting accuracy is verified. Single-objective and multi-objective optimization are conducted based on the response surface model, respectively. And the multi-objective optimization for the gasket can successfully reduce the two bearings' stress to the value below the bearing material's yield strength. In addition, to check the optimization's effectiveness, an experiment is carried out and the results indicate that the gasket whose axial thickness and elastic modulus have been optimized can effectively improve the rotating rack's performance of withstanding impact loadings.